Deformation analysis of wing structures - Kuhn, Paul (National Advisory Committee for Aeronautics, 1947)
The elementary theories of bending and torsion often do not describe the stresses in aircraft shell structures with adequate accuracy; more refined stress theories have therefore have developed over a period of years. Theories of this nature are applied to the problem of calculating the deflections, particularly of wings. Bending as well as torsional deflections are discussed for wings without or with cut-outs. Whenever convenient, the formulas are given in such a form that they yield corrections to be added to the deflections calculated by means of the elementary theories. Examples show that the deflection corrections usually are quite small; very simple approximation formulas are therefore adequate for design purposes when conventional structures uder a reasonably uniform loading are being considered.
"Langley Memorial Aeronautical Laboratory."
Date of issue: July 1947.
Report no. NACA TN No. 1361.
Keywords: Deformations (Mechanics); Airplanes -- Wings.; Strains and stresses.; Mathematics -- Formulae.; elektronické knihy; electronic books